Proceedings of International Symposium on Sensor Networks, Systems and Security Advances in Computing and Networking with Applications - Rao, Nageswara S.V.; Brooks, Richard R.; Wu, Chase Q.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents current trends that are dominating technology and society, including privacy, high performance computing in the cloud, networking and IoT, and bioinformatics. By providing chapters detailing accessible descriptions of the research frontiers in each of these domains, the reader is provided with a unique understanding of what is currently feasible. Readers are also given a vision of what these technologies can be expected to produce in the near future. The topics are covered comprehensively by experts in respective areas. Each section includes an overview that puts the research topics in perspective and integrates the sections into an overview of how technology is evolving. The book represents the proceedings of the International Symposium on Sensor Networks, Systems and Security, August 31 - September 2, 2017, Lakeland Florida.
Introduction -- Part I: Privacy and game theory -- A Novel Perfect Privacy PIR scheme for Privacy Critical Applications -- Heterogeneous Sensor Privacy Protection with Stackelberg Privacy Games -- Intelligent Access Control: A Self-Adaptable Trust Based Access Control Framework (SATBAC) using Game Theory Strategy -- Public Key Cryptosystem for Privacy Sensitive Location Based Services -- Stochastic Tools for Network Intrusion Detection -- Part II: High performance computing and the cloud -- Accelerating the Big Data Analytics by GPU based Machine Learning: A Survey -- Multimedia Data Management for Disaster Situation Awareness -- On the Need of Security Standards in Big Data Information Flow -- Using Markov models and statistics to learn, extract, fuse, and detect patterns in raw data -- Dynamic Firewall Policy Management Framework for Private Cloud -- Security threats and solutions for virtualization and migration in virtual machines -- Techniques to certify integrity and proof of existence for a periodical re-encryption based long term archival systems -- Part III: Networking and the Internet of Things (IoT) -- A Study of Contact Durations for Vehicle to Vehicle Communications -- Evolution of Sensors leading to Smart Objects and Security Issues in IoT -- Flexible Bandwidth Scheduling for Streaming Data Movement Over Dedicated Networks -- Internet of Things: Current Trends and Emerging Prospects -- Measurements and Analytics of Data Transport Over Dedicated Connections -- Trends and Future Directions of Research for Smart Grid IoT Sensor Networks -- SCADA: Analysis of Attacks on Communication Protocols -- Part IV: Bioinformatics -- TASB-AC: Term Annotated Sliding-window based Boosting Associative Classifier for DNA Repair Gene Categorization -- Temporal analysis of stress classification using QRS complex of ECG signals -- Conclusion.
Keywords: Telecommunication; Signal processing; Computer networks .; Data protection; Communications Engineering, Networks; Signal, Speech and Image Processing .; Computer Communication Networks; Data and Information Security